2021
DOI: 10.1021/acs.jmedchem.0c02188
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Potent and Orally Active Isoindolinone Inhibitors of MDM2-p53 Protein–Protein Interaction

Abstract: Inhibition of murine double minute 2 (MDM2)-p53 protein−protein interaction with small molecules has been shown to reactivate p53 and inhibit tumor growth. Here, we describe rational, structure-guided, design of novel isoindolinone-based MDM2 inhibitors. MDM2 X-ray crystallography, quantum mechanics ligand-based design, and metabolite identification all contributed toward the discovery of potent in vitro and in vivo inhibitors of the MDM2-p53 interaction with representative compounds inducing cytostasis in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…It is obvious that targeted therapy plays a critical role in the treatment of osteosarcoma. In an SJSA-1 osteosarcoma xenograft model, Chessari et al discovered a potent isoindolinone inhibitor of the MDM2-p53 interaction, which demonstrated critical anticancer efficacy [15]. Trametinib and trastuzumab, two MEK inhibitors, were investigated in a phase I/II clinical study and a phase II clinical study for osteosarcoma or recurrent osteosarcoma, respectively [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that targeted therapy plays a critical role in the treatment of osteosarcoma. In an SJSA-1 osteosarcoma xenograft model, Chessari et al discovered a potent isoindolinone inhibitor of the MDM2-p53 interaction, which demonstrated critical anticancer efficacy [15]. Trametinib and trastuzumab, two MEK inhibitors, were investigated in a phase I/II clinical study and a phase II clinical study for osteosarcoma or recurrent osteosarcoma, respectively [16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of pharmaceuticals that incorporate in their structure an aldehyde functionality are currently in clinical use and, furthermore, toxicity arising from the presence of the aldehyde is context-specific, 26 as is presumably the case here. Finally, the present study also sought to exploit the kinetic isotope effect associated with the H/D bioisosteric replacement [27][28] in order to dampen oxidative metabolism at the -CH2O-metabolic soft spot in the inhibitors, 29 as well as to reduce toxicity. Thus, the availability of equipotent deuterated analogs that display improved PK characteristics enhances further the significance of the results reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…The second is the peptidomimetic design of peptide-like molecules to mimic the 3D structures of the original protein-protein interaction interfaces for the sake of competitive inhibition and subsequent disruption ( Wang et al, 2021 ). Structure-based design strategies were previously applied in the successful identification of protein-protein interaction inhibitors, for instance, small molecule inhibitors for the interaction of Myeloid Leukemia 1 (Mcl-1) with BH3-containg peptides ( Kotschy et al, 2016 ), small molecule inhibitor ( Chessari et al, 2021 ) and p53 α-helical peptide mimetic inhibitor ( Chen et al, 2005 ) of p53 interaction with Mdm2.…”
Section: Challenges and Strategies For Targeting Protein-protein Inte...mentioning
confidence: 99%